Knowledge regarding Hypothyroidism among Community People of Kavre - Pote, Riya; Bhandari, Bhawana; Jha, Jyanendra; Mishra, Rupesh; Yakha, Bhim Maya; Dangol, Anamika; Giri, Moushami; Ojha, Anil Babu (Journal of Advanced Academic Research, 2023)
Background: Hypothyroidism is a condition in which the thyroid gland is unable to produce enough thyroid hormone. Thyroid dysfunction is one of the concern public health problem among the Nepalese population. It has been estimated that 0.2% of the deaths in Nepal result from endocrine disorders, among which Iodine deficiency has been a major cause. Therefore, this study helps to assess knowledge level regarding hypothyroidism among community people of Banepa-8, Kavre. Objectives: To assess the knowledge regarding hypothyroidism and to identify the association of knowledge with the selected demographic variables. Methodology: A descriptive cross-sectional study was conducted among 140 respondents of Banepa-8, Kavre district on April 2021. All the adult people of age 25-55 years were included in the study. Structured knowledge questionnaire was used after validity and reliability. Data was collected by interview Result: Among the 140 participants, statistical analysis showed that more than half of the respondents 46(37.9%) had low knowledge, majority 87(62.1%) of respondents had average knowledge and 7 (5%) had high knowledge regarding Hypothyroidism. Age, Gender, education, ethnicity, occupation, family history and marital status had no significant effect on the knowledge level of the respondents at (p > 0.05). Conclusion: Knowledge regarding hypothyroidism was found to be average among majority of people in Banepa-8, Kavre. There was no significant association with the knowledge and selected demographic variables.